Neurorehabilitation Success: How Personality Influences Recovery - Saadati, Seyed Alireza (Journal of Personality and Psychosomatic Research (JPPR), 2024)
Neurorehabilitation is a critical aspect of recovery for individuals who have suffered neurological injuries or conditions, such as stroke, brain tumors, and acquired brain injuries. While the effectiveness of various neurorehabilitation techniques has been extensively studied, the role of personality in influencing recovery outcomes remains an intriguing and underexplored area. This letter aims to highlight the significance of personality traits in neurorehabilitation success and to suggest how incorporating personality assessments into rehabilitation programs can enhance recovery outcomes. Personality traits play a crucial role in influencing neurorehabilitation outcomes. By incorporating personality assessments into rehabilitation programs, clinicians can develop personalized interventions that cater to the unique needs of each patient. This approach can enhance engagement, adherence, and ultimately, recovery outcomes. Future research should continue to explore the interplay between personality and neurorehabilitation, with a focus on developing tailored therapeutic strategies that maximize the potential for recovery.